Changes in United States Latino/a High School Students’ Science Motivational Beliefs: Within Group Differences Across Science Subjects, Gender, Immigrant Status, and Perceived Support - Hsieh, Ta-yang; Liu, Yangyang; Simpkins, Sandra D. (Frontiers in Psychology, 2019)
Science motivational beliefs are crucial for STEM (science, technology, engineering, and math) performance and persistence, but these beliefs typically decline during high school. We expanded the literature on adolescents’ science motivational beliefs by examining: 1) changes in motivational beliefs in three specific science subjects, 2) how gender, immigrant generation status, and perceived support from key social agents predicted differences in adolescents’ science motivational beliefs, and 3) these processes among Latino/as in the United States, whose underrepresentation in STEM is understudied. We used hierarchical linear modeling to estimate the changes in 104 (40% female) Latino/a high school students’ physics, chemistry, and biology motivational beliefs from 9th to 11th grade. Subject-specific ability self-concept, interest, and utility were regressed on gender, immigrant generation status, and perceived science support while controlling for family income, parent education, and adolescents’ school. Adolescents’ utility declined from 9th to 11th grade whereas their interest remained stable for all three science subjects. Adolescents’ ability self-concept increased for biology, decreased for physics, but remained stable for chemistry. Gender differences in adolescents’ motivational beliefs at 9th grade only emerged for physics utility as well as physics and chemistry interest; yet, there were no gender differences in how adolescents’ science motivational beliefs changed over time. Contrary to expectations, immigrant generation status was not significantly associated with adolescents’ science motivational beliefs at 9th grade or in terms of how they changed over time. Adolescents who perceived higher science support generally had higher motivational beliefs in 9th grade, but did not differ on their rate of change. Our findings highlight the need to examine specific science subjects, and that typical gender differences in adolescents’ motivational beliefs discussed in the literature may not generalize to all racial and ethnic groups.